Costa, Costas - (:unkn) unknown (My University, 2026)
Dr. Costa is a Professor at the Department of Environmental Science and Technology of the School of Geotechnical Sciences and Environmental Management. He has obtained his BSc and MSc in Chemistry and his PhD in Environmental Catalysis from the University of Cyprus. During his Academic Career he has obtained several National and International honors and awards for his academic and research achievements, including an Honor from the Denmark Royal Academy of Sciences for the development of a Novel Sustainable de-pollution technology. He has worked as a Research Fellow at the University of Manchester Institute of Technology (UMIST) and as a Postdoctoral Fellow, Visiting Lecturer and Assistant Professor at the University of Cyprus (Department of Chemistry). Dr. Costa has more than 45 publications in High Impact, International, Refereed Journals, while he also has over 55 publications in International Conferences Proceedings, where he participated for presentation of his research. He is currently the Coordinator of five (3) European Research Projects, while he participated in more than 30 Research Projects (European, UNOPs, Leonardo, Cyprus Research Promotion Foundation), in 13 of which he was the coordinator (Lead Partner). He owns six (6) patents (European, USA, Japan) for the Development of Novel Technologies for the Reduction of Nitrogen Oxides (NOX) with bio-ethanol and/or hydrogen. Part of the Intellectual Rights of the latter technology has been licensed to the largest Company in the field De-pollution Technologies, worldwide. The latter patented technology is expected to be commercialized (by means of a novel environmental application) within the next three to five years.